2010
DOI: 10.1590/s1806-37132010001400010
|View full text |Cite
|
Sign up to set email alerts
|

Alterações cognitivas na SAOS

Abstract: ResumoAlterações da cognição e do desempenho estão bem estabelecidas em pacientes com SAOS, causando um impacto significativo sobre a qualidade de vida e o risco de acidentes nesses indivíduos. Tais alterações são mais profundas nos quadros mais graves de SAOS, o que explica a aparente discrepância na frequência e gravidade desse prejuízo entre estudos com pacientes de clínicas de sono e estudos de base populacional. Vários aspectos podem estar comprometidos, incluindo o processamento cognitivo, a atenção sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Additionally, OSA is a multisystem chronic disease that is often associated with a variety of other diseases, such as cardiovascular disease,6 hypertension, stroke, chronic kidney disease,7 depression,8 anxiety, insomnia, and even Alzheimer’s disease (AD) 9. Furthermore, cognitive dysfunction has been observed in patients with OSA, including deficits in attention, memory, executive functions, emotion, visuospatial function,10 psychomotor speed, fine coordination, and language ability 11,12. The cognitive impairment observed in OSA patients is generally believed to be caused by adverse effects of long-term exposure to chronic intermittent hypoxia13 and sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, OSA is a multisystem chronic disease that is often associated with a variety of other diseases, such as cardiovascular disease,6 hypertension, stroke, chronic kidney disease,7 depression,8 anxiety, insomnia, and even Alzheimer’s disease (AD) 9. Furthermore, cognitive dysfunction has been observed in patients with OSA, including deficits in attention, memory, executive functions, emotion, visuospatial function,10 psychomotor speed, fine coordination, and language ability 11,12. The cognitive impairment observed in OSA patients is generally believed to be caused by adverse effects of long-term exposure to chronic intermittent hypoxia13 and sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aberrant spontaneous brain activity in the whole brain or regional areas has been confirmed through resting-state functional magnetic resonance imaging (rs-fMRI) methods in patients with OSA 2126. Published studies have identified that OSA patients have impaired attention, memory, emotion, and executive functions, which are correlated with multiple brain regions including the amygdala, insular cortex, cingulate cortex, frontal regions, thalamus, temporal region, hippocampus, cerebellum, and precuneus 10,27…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system symptoms, with excessive daytime sleepiness being the main clinical symptom (Dostálová et al, 2012;Tóthová et al, 2015), severely limit everyday life activities and, in some cases, leads to disability. In older SAS patients especially, associated memory problems and depression can further worsen the quality of life (Bruin and Bagnato, 2010;Onen and Onen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SA usually present witnessed episodes of snoring, choking, and are more likely to suffer from daytime sleepiness ( 1 ), depression ( 2 , 3 ) and are at increased risk of motor vehicle crash ( 4 ), and occupational accidents ( 5 ). Other important adverse consequences of SA include neuropsychiatric disorders, such as cognitive impairment ( 6 ), abnormal sympathetic activity ( 7 ), and cardiovascular abnormalities such as hypertension ( 8 ), stroke, and arterial obstruction ( 9 ).…”
Section: Introductionmentioning
confidence: 99%